MYC Inactivation Elicits Oncogene Addiction through Both Tumor Cell–Intrinsic and Host-Dependent Mechanisms - Felsher, Dean W. (SAGE Publications, 2010)
Tumorigenesis is generally caused by genetic changes that activate oncogenes or inactivate tumor suppressor genes. The targeted inactivation of oncogenes can be associated with tumor regression through the phenomenon of oncogene addiction. One of the most common oncogenic events in human cancer is the activation of the MYC oncogene. The inactivation of MYC may be a general and effective therapy for human cancer. Indeed, it has been experimentally shown that the inactivation of MYC can result in dramatic and sustained tumor regression in lymphoma, leukemia, osteosarcoma, hepatocellular carcinoma, squamous carcinoma, and pancreatic carcinoma through a multitude of mechanisms, including proliferative arrest, terminal differentiation, cellular senescence, induction of apoptosis, and the shutdown of angiogenesis. Cell-autonomous and cell-dependent mechanisms have both been implicated, and recent results suggest a critical role for autocrine factors, including thrombospondin-1 and TGF-β. Hence, targeting the inactivation of MYC appears to elicit oncogene addiction and, thereby, tumor regression through both tumor cell–intrinsic and host-dependent mechanisms.